PERAN LEMBAGA KONSULTASI KESEJAHTERAAN KELUARGA TAT TWAM ASI DALAM PENANGANAN MASALAH KELUARGA - Riska Siregar; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to describe the role of the Family Welfare Consultation Institution Tat Twam Asi in the handling of family social problems in Pekanbaru City. This research uses qualitative approach and with descriptive method. The subject of this research is Chairman of LK 3 Tat Twam Asi, Social Worker in LK3 Tat Twam Asi. The data were collected using observation, interview, and documentation techniques. Techniques used in data analysis are data reduction, data presentation, and conclusion. The technique used to explain the validity of data is by using triangulation of source and triangulation technique.Based on the research results obtained are: the role of the Family Welfare Consultation Institution Tat Twam Asi in handling family problems through several stages namely, client recruitment that includes clients coming by themselves and picking up the ball, and handling clients that include counseling, home visit, empowerment and referrals. The role of LK3 in handling problems in the family there are several kinds of prevention, empowerment, protection and client assistance.Keyword : Social Role, LK 3, Pekanbaru, Riau